Investigating the role of routine drug analyses in survivors of sexual offences admitted to the clinical forensic unit at Victoria Hospital - Peters, Casey (Department of Pathology, 2025)
Introduction: Toxicological analysis is an important component of drug-facilitated sexual assault (DFSA) investigations, as it allows for identification and interpretation of substances involved. Currently, forensic toxicological analyses are not routinely provided to DFSA survivors in South Africa. The aim of this study was to investigate the utilisation and applicability of a targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for common drugs of abuse in cases of suspected drug facilitated sexual offences. Methods: Blood and urine samples from 17 consenting adult survivors, who reported to the Clinical Forensic Unit at Victoria Hospital (August 2022 – December 2022) in Cape Town, South Africa, were analysed using a validated LC-MS/MS method targeting 31 common drugs of abuse. Samples were prepared for analysis using a Waters Ostro® pass-through plate extraction for blood and simple dilution extraction for urine. Case histories were obtained from participants by the attending medical practitioner using a standardised data collection sheet. Results: Majority of the participants reported to the clinic within 24 hours after the alleged offence (64.7%). Several participants reported consuming alcohol (64.7%), medicinal drugs (23.5%), or recreational drugs (35.3%) prior to, or at the time of the offence. A psychoactive drug was detected in 58.8% of cases. Methamphetamine (and its metabolite amphetamine) were the most frequently detected analytes (41.2% and 35.3% of cases, respectively). Conclusion: Accurate and reliable toxicological analysis is vital in processing DFSO cases. This study determined that the analytical method is useful in DFSO cases as over half of the participants tested positive for at least one drug, and most self-reported recreational drugs were included in the panel. Recommendations include expanding the panel to include additional pharmaceutical drugs and incorporating ethanol analysis into the routine workflow to provide comprehensive testing to survivors of DFSO and support the criminal justice system in South Africa.